1865-66 Ala. Laws 7 - (:unkn) unknown (My University, 1866)
§ 2, pt. 11: Imposed an annual tax of two dollars on each person who is not a regular dealer but in possession of pistols and revolvers. Imposed an annual tax of three dollars on each person who is not a regular dealer but in possession of bowie knives or knives of like description.
Keywords: TAX - PROPERTY OR SALES